Konselink: A Task Management, Motivation, and Counseling Application - Anggara, Rayyen Tri; Putra, Alfian Eka; Azis, Satriadi (Journal of Security, Computer, Information, Embedded, Network, and Intelligence System, 2025)
The integration of technology into education and counseling has become essential in improving the quality of support services for students. This study aims to develop Konselink, a digital application that combines task management, motivational content, and counseling features as a holistic solution to address students’ productivity and mental well-being needs. The development method follows the Software Development Life Cycle (SDLC) using the spiral model approach, emphasizing risk evaluation and iterative progress across stages. The development process includes planning features based on literature review, risk analysis, technical engineering, and limited user evaluation. The result is an application with five main features: a login/register page for user authentication, a task list for managing assignments, an inspiration page displaying motivational videos linked to YouTube, a counseling feature integrated with WhatsApp, and a profile page for account settings. Initial evaluation indicates that Konselink helps users manage their time efficiently, gain emotional encouragement, and access counseling services practically. In conclusion, Konselink provides an innovative approach to supporting academic success and student mental health through accessible and relevant digital technology integration.